2019
DOI: 10.1002/jor.24557
|View full text |Cite
|
Sign up to set email alerts
|

Development of an in vitro intervertebral disc innervation model to screen neuroinhibitory biomaterials

Abstract: Pain originating from an intervertebral disc (discogenic pain) is a major source of chronic low back pain. Pathological innervation of the disc by pain-sensing nerve fibers is thought to be a key component of discogenic pain, so treatment with biomaterials that have the ability to inhibit neurite growth will greatly benefit novel disc therapeutics. Currently, disc therapeutic biomaterials are rarely screened for their ability to modulate nerve growth, mainly due to a lack of models to screen neuromodulation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Pathological innervation of the disc by pain-sensing nerve fibers is thought to be a key component of discogenic pain [35,36]. In this study, we found that IVDD mice exhibited a significant increase in the number of Cgrp + sensory nerves both in outer AF and ectopic bone formation zone, and WBV treatment further increases the density of Cgrp + sensory nerves in outer AF.…”
Section: Discussionsupporting
confidence: 48%
“…Pathological innervation of the disc by pain-sensing nerve fibers is thought to be a key component of discogenic pain [35,36]. In this study, we found that IVDD mice exhibited a significant increase in the number of Cgrp + sensory nerves both in outer AF and ectopic bone formation zone, and WBV treatment further increases the density of Cgrp + sensory nerves in outer AF.…”
Section: Discussionsupporting
confidence: 48%
“…Inner gels consisted of either regelled NP or type I collagen. Collagen inner gels were used as a positive control due to its neuro‐permissive properties 45,56 . To prepare the model, regelled NP and collagen gels were prepared as previously described herein with a final collagen concentration of 3.6 mg/ml, to match the final regelled NP collagen concentration which equates to the summation of the added type I collagen (2.5 mg/ml), and the collagen from the digested tissue (1.1 mg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…To accurately model the growth of DRG neurons into a degenerative disc in vitro, we utilized our previously established gel‐within‐gel 3D culture method to model the in vivo environment of the DRG and NP. 45 Cut DRGs were embedded and cultured in type I collagen outer hydrogel that surrounded an inner “NP‐like” gel. Inner gels consisted of either regelled NP or type I collagen.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations